ECONOMY OF RECIPROCITY: THE WELL-FORGOTTEN NEW - Irina P. Komarova; Ekaterina S. Novikova; Elena V. Ustyuzhanina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article investigates present day trends of joint consumption economy or economy of reciprocity from the point of view of institutional and economic theory. It analyzes modern approaches to understanding of this economic category, puts forward the authors’ definition of economy of reciprocity, shows key types of joint use of resources, studies the idea of reciprocity within the frames of the given economic approach and demonstrates prospects of economy of reciprocity development. Investigation of information technologies’ impact on the economy of reciprocity development is especially acute. In particular, the authors pay attention to the fact that today many functions of regulating interrelations between participants are transferred to information platforms through which interaction of economic agents takes place.